2005
DOI: 10.1007/s00439-004-1245-0
|View full text |Cite
|
Sign up to set email alerts
|

Unusual segregation products in sperm from a pericentric inversion 17 heterozygote

Abstract: Chromosome segregation and interchromosomal effect were studied in spermatozoa from a carrier of a pericentric chromosome 17 inversion, 46,XY,inv(17)(p13.1q25.3). Sperm chromosome segregation, lymphocytes of the inversion carrier, and cells from his offspring were analysed by multicolour fluorescence in situ hybridization. The frequency of balanced sperm was 73%. An unusual segregation of recombinants was observed, viz. deletion of the p arm (14.6%) or duplication of the p arm with the presence of one q arm (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Data show divergent results regarding the occurrence and distribution of ICE among carriers. Whereas some authors have observed a significant increase of numerical abnormalities for many of the chromosomes analyzed [Rousseaux et al 1995a;Rousseaux et al 1995b;Van Hummelen et al 1997;Blanco et al 1998;Mercier et al 1998;Blanco et al 2000;Amiel et al 2001;Morel et al 2001;Oliver-Bonet et al 2001;Baccetti et al 2002;Oliver-Bonet et al 2002;Anton et al 2004a;Anton et al 2004b Machev et al 2005;Anton et al 2006;Chen et al 2007;Wiland et al 2007;Anton et al 2008;Vozdova et al 2008;Juchniuk de Vozzi et al 2009;Anton et al 2010;Pellestor et al 2011;Vozdova et al 2011b], others have not [Martini et al 1998;Cifuentes et al 1999;Honda et al 1999;Estop et al 2000;Rives et al 2003;Mikhaail-Philips et al 2004;Oliver-Bonet et al 2004;Mikhaail-Philips et al 2005;Hatakeyama et al 2006;Kekesi et al 2007;Vialard et al 2007].…”
Section: Interchromosomal Effectmentioning
confidence: 96%
“…Data show divergent results regarding the occurrence and distribution of ICE among carriers. Whereas some authors have observed a significant increase of numerical abnormalities for many of the chromosomes analyzed [Rousseaux et al 1995a;Rousseaux et al 1995b;Van Hummelen et al 1997;Blanco et al 1998;Mercier et al 1998;Blanco et al 2000;Amiel et al 2001;Morel et al 2001;Oliver-Bonet et al 2001;Baccetti et al 2002;Oliver-Bonet et al 2002;Anton et al 2004a;Anton et al 2004b Machev et al 2005;Anton et al 2006;Chen et al 2007;Wiland et al 2007;Anton et al 2008;Vozdova et al 2008;Juchniuk de Vozzi et al 2009;Anton et al 2010;Pellestor et al 2011;Vozdova et al 2011b], others have not [Martini et al 1998;Cifuentes et al 1999;Honda et al 1999;Estop et al 2000;Rives et al 2003;Mikhaail-Philips et al 2004;Oliver-Bonet et al 2004;Mikhaail-Philips et al 2005;Hatakeyama et al 2006;Kekesi et al 2007;Vialard et al 2007].…”
Section: Interchromosomal Effectmentioning
confidence: 96%
“…Investigations into the production of unbalanced gametes in balanced inversion carriers have been made to a much lesser extent than translocations; nevertheless, a handful of studies have reported ranges of unbalanced sperm of 1%-54%. [55][56][57][58][59] INTERCHROMOSOMAL EFFECT (ICE) Interestingly, the presence of a structural chromosomal aberration has in many cases exhibited an increased frequency of chromosomal abnormalities that involve chromosomes other than those involved in the rearrangement (reviewed by Ref. 60).…”
Section: Chromosomal Inversionsmentioning
confidence: 99%
“…Of note, an identical type of duplication was described in a child presenting a de novo inv dup(17p), localized to the terminal region of the long arm of the same chromosome, with a breakpoint on 17q distal to the 17q subtelomeric probe [Paskulin et al, ]. Meiotic recombination of a parental pericentric inversion, with a 17q breakpoint between the q arm telomere‐associated repeats and the q subtelomere region, had been suggested to be involved in the etiology of this chromosomal rearrangement, a mechanism that was previously reported [Lurie et al, ; Mikhaail‐Philips et al, ]. The recurrent nature of all these similar recombinants, including our dup(1q), suggests an identical mechanism of formation, resulting in pure duplications.…”
Section: Discussionmentioning
confidence: 89%